Biedaczyna krakowski – obraz Alberta Chmielowskiego w czasopismach zakładu albertynów - Klimek-Grądzka, Jolanta (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article analyses prosaic and poetic texts published in the years 1932-1939 in two journals run by the Cracow-based Albertine educational facility. The analysis aims to draw a language image of Adam Chmielowski – Brother Albert. The researched texts reveal the domination of the pragmaticsemantic profiles relating to his spiritual life and monastic activity: saint, monk, founder of the congregation, master and mentor, servant of the poor. Such profiles as artist or friend stay in the background. The lexical network that founds the discovered profiles and the positive evaluative utterances that fill the network build a consistent language image of Brother Albert, who had been regarded as a saint before his official beatification.